2019
DOI: 10.3390/biom9010014
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Mechanism of Low Doses of NaGdF4:Yb3+,Er3+ Upconverting Nanoparticles in Activated Macrophage Cell Lines

Abstract: Gadolinium-doped nanoparticles (NPs) are regarded as promising luminescent probes. In this report, we studied details of toxicity mechanism of low doses of NaGdF4-based fluorescent nanoparticles in activated RAW264.7, J774A.1 macrophages. These cell lines were specifically sensitive to the treatment with nanoparticles. Using nanoparticles of three different sizes, but with a uniform zeta potential (about −11 mV), we observed rapid uptake of NPs by the cells, resulting in the increased lysosomal compartment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
2
20
0
Order By: Relevance
“…However, adding potentially hazardous fluoride ions is not an option for applying UCNP in biological systems. Nanoparticle concentrations commonly used in in-vitro studies range from 1 to 100 ppm (µg/mL) 19,20,56 . Verma et al showed that fluoride concentrations of 120 ppm decreased cell viability up to 60% 57 .…”
Section: Resultsmentioning
confidence: 99%
“…However, adding potentially hazardous fluoride ions is not an option for applying UCNP in biological systems. Nanoparticle concentrations commonly used in in-vitro studies range from 1 to 100 ppm (µg/mL) 19,20,56 . Verma et al showed that fluoride concentrations of 120 ppm decreased cell viability up to 60% 57 .…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the cell viability of silica-coated particles is higher than that of non-coated NaGdF 4 nanoparticles. Wysokińska et al investigated such particles, with average sizes between 4 and 249 nm and IC 50 values below 2 µg/mL, via 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2 H -tetrazolium (MTS) assays [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, the cytotoxicity of UCNP cores coated with silica shells was investigated in the macrophage cell line RAW 264.7. RAW 264.7 cells are particularly sensitive to the treatment with nanoparticles [42][43][44]. They are an established model of activated macrophages and they actively take up nanomaterials from biological media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be related with the high phagocytic activity of macrophages accumulating a great variety of nanomaterial. This results in a greater sensitivity to treatments with particulate matter [44]. On the other hand, the cause of selectivity could be related to expression of scavenger receptors on macrophages [45,46].…”
Section: Discussionmentioning
confidence: 99%